PELAKSANAAN PENGAWASAN BALAI BESAR PENGAWASAN OBAT DAN MAKANAN (BBPOM) TERHADAP PEREDARAN MAKANAN DAN MINUMAN TANPA IZIN EDAR (TIE) DI KOTA PEKANBARU TAHUN 2012 - Meliza Edtriani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Center for Food and Drug Administration ( BBPOM ) is an institution in Indonesia which oversees the distribution of medicinal products , traditional medicines , cosmetics , dietary supplements and food throughout the Indonesian region that products that are not fit for consumption or does not meet the standards are not circulating in the area Indonesia . Government Regulation No. 28 of 2004 on 's security , quality , and nutritional food , need to establish regulatory supervision of the head of the food and drug supervision processed food intake . Rule number 329/menkes/per/XII/76 health minister about the production and distribution of food . and PP . 69 Year 1999 on food label and advertisement mentions " each person knowingly manufactures or produces packaged food in the region appears logical to be traded on the label must include , on the inside, and or packaging food ".In this study the authors use qualitative data collection techniques , data collection on natural conditions , sources of primary data and secondary data , and more data collection techniques in participatory observation , in-depth interviews . Supervision of food and beverages without a marketing authorization in the city of Pekanbaru rated " satisfactory" It can still be seen without the presence of food and beverage marketing authorization in the market , existence of obstacles presented by the Center for POM Pekanbaru an obstacle in conducting surveillance.Keywork : Pengawasan, Balai Besar Pengawasan Obat dan Makanan (BBPOM), Peredaran